Odpowiedzi

Najlepsza Odpowiedź!
2010-04-06T23:56:40+02:00
A)
x+y=9
x-y=3
-------
2x=12
x=6

6+y=9
y=9-6
y=3

b)
3x+2y=2
-3x+y=10
-----------
3y=12
y=4

3x+2*4=2
3x=2-8
3x=-6
x=-2

c)
3x+2y=5
2x+2y=2|*(-1)

3x+2y=5
-2x-2y=-2
-----------
x=3

3*3+2y=5
2y=5-9
2y=-4
y=-2

d)
x+4y=11|*(-2)
2x+5y=10

-2x-8y=-22
2x+5y=10
-----------
-3y=-12
y=4

x+4*4=11
x=11-16
x=-5

e)
4x+5y=-4|*3
6x+7y=-6|*(-2)

12x+15y=-12
-12x-14y=12
-------------
y=0

4x+5*0=-4
4x=-4
x=-1

f)
2x-11y=73|*4
3x-4y=47|*(-11)

8x-44y=292
-33x+44y=-517
----------------
-25x=-225
x=9

2*9-11y=73
-11y=73-18
-11y=55
y=-5

g)
-2x+5y=-10|*7
7x-4y=8|*2

-14x+35y=-70
14x-8y=16
-----------
27y=-54
y=-2

-2x+5*(-2)=-10
-2x=-10+10
-2x=0
x=0

h)
9x+8y=1|*3
5x-6y=11|*4

27x+24y=3
20x-24y=44
-------------
47x=47
x=1

9*1+8y=1
8y=1-9
8y=-8
y=-1